Optimizing Student Participation in Waste Management as an Effort to Increase Awareness of a Waste-Free Environment - Meidinda Ardiani Putri; Putri, Inge Wiliandani Setya; Wardoyo, Arik Aguk; Durunnafis, Alyya Oktavia; Salsabila, Salma (International Assulta of Research and Engagement (IARE), 2024)
Waste management is crucial in maintaining environmental cleanliness and the health of living things around it. At SD Negeri Glagahwero 01, waste problems are a major concern in maintaining the cleanliness of the school environment. This community service aims to educate students about their role in waste management and increase awareness of a waste-free environment. This research method uses Participatory Action Research (PAR) through training with material presentation, active interaction, contextual learning, and discussions involving grade 6 students of SD Negeri Glagahwero 01 and the Kampus Mengajar 7 team. In the socialization, students were invited to recognize the types of waste and how to manage the waste around them. The results of the community service show that this activity has succeeded in attracting and educating students about waste management. They responded positively by answering the speakers' questions and providing examples of waste management that they can do correctly in their daily lives. In addition, students also understand the impact of good and bad waste management. Although the socialization is short, this activity can influence student behavior in the long term so that they are aware of their role in creating a waste-free environment.